The Association Between Maternal Roles as Educators, Role Models, and Companions and Vulva Hygiene Practices Among Adolescent Girls - Tri Anggraini; Arie Kusumaningrum; Nurna Ningsih (Nursing Information Journal, 2026)
Misconceptions and improper practices in vulva hygiene among adolescent girls are often linked to inadequate maternal support. This study aimed to examine the association between maternal roles as educators, role models, and companions and vulva hygiene practices among adolescent girls in Indonesia. This study is A cross-sectional analytical survey that was conducted with 102 mother-daughter pairs selected through simple random sampling from a public high school in South Sumatra. Data were collected via structured questionnaires and analyzed using the chi-square test, with Prevalence Ratios (PR) and 95% confidence intervals calculated to measure association strength. Significant associations were found between maternal roles and good vulva hygiene practices: educator role (p=0.033, PR=1.93, 95% CI: 1.03–3.63), role model (p=0.028, PR=2.00, 95% CI: 1.03–3.87), and companion (p=0.036, PR=1.89, 95% CI: 1.03–3.46). Socioeconomic status was also significantly associated with maternal role quality (p=0.030), and mothers with higher education, greater knowledge, and authoritative parenting styles were more effective in supporting their daughters’ hygiene. In conclusion, maternal involvement in multiple roles significantly influences vulva hygiene practices among adolescent girls. Health education programs should integrate maternal engagement strategies to improve adolescent reproductive health outcomes.